Sepsis and Neutropenia in Very Low Birth Weight Infants Delivered of Mothers with Preeclampsia - Procianoy, Renato S.; Silveira, Rita C.; Mussi-Pinhata, Marisa M.; Souza Rugolo, Ligia Maria S. [UNESP]; Leone, Clea R.; de Andrade Lopes, Jose Maria; de Almeida, Maria Fernanda B. (Mosby-elsevier, 2010)
Objective To study the association between maternal preeclampsia and neonatal sepsis in very low birth weight newborns.Study design We studied all infants with birth weights between 500 g and 1500 g who were admitted to 6 neonatal intensive care units of the Brazilian Network on Neonatal Research for 2 years. Exclusion criteria were major malformations, death in the delivery room, and maternal chronic hypertension. Absolute neutrophil count was performed in the first 72 hours of life.Results A total of 911 very low birth weight infants (preeclampsia, 308; non-preeclampsia, 603) were included. The preeclampsia group had significantly higher gestational age, more cesarean deliveries, antenatal steroid, central catheters, total parenteral nutrition, and neutropenia, and less rupture of membranes >18 hours and mechanical ventilation. Both groups had similar incidences of early sepsis (4.6% and 4.2% in preeclampsia and non-preeclampsia groups, respectively) and late sepsis (24% and 22.1% in preeclampsia and non-preeclampsia groups, respectively). Vaginal delivery and neutropenia were associated with multiple logistic regressions with early sepsis, and mechanical ventilation, central catheter, and total parenteral nutrition were associated with late sepsis. Death was associated with neutropenia in very preterm infants.Conclusions Preeclampsia did not increase neonatal sepsis in very low birth weight infants, and death was associated with neutropenia in very preterm infants. (J Pediatr 2010; 157: 434-8).